Respuesta :

Answer:

  [tex]\log_2{\left(\dfrac{x^2z}{y^2}\right)}+\log_9{(x^{12}y^4)}[/tex]

Step-by-step explanation:

The appropriate rules of logarithms are ...

  log(a)+log(b) = log(ab)

  n·log(a) = log(a^n)

We can use these rules to combine the logs to the same base so each is a log of a single expression.

[tex]\log_2{z}+2\log_2{x}+4\log_9{y}+12\log_9{x}-2\log_2{y}\\\\=\log_2{(z\cdot x^{2}\cdot y^{-2})}+\log_9{(y^{4}\cdot x^{12})}\\\\=\log_2{\left(\dfrac{x^2z}{y^2}\right)}+\log_9{(x^{12}y^4)}[/tex]